Generation brave : the Gen Z kids who are changing the world - Alexander, Kate (Andrews McMeel Publishing, 2020)
Profiles dozens of young social activists from Generation Z, including Simone Biles, Haile Thomas, and Greta Thunberg. Highlights the activism of these Generation Z figures and the areas they are fighting fore, including minority rights and climate change.